2018
DOI: 10.1007/s10646-018-1935-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of exposure to the juvenile hormone analog fenoxycarb during sexual reproduction in Daphnia magna

Abstract: Recent studies have demonstrated that insect growth regulating insecticides are able to affect reproductive endpoints in zooplankton species at very low levels. For the cyclic parthenogenetic water flea Daphnia, most of this research has focused on the asexual part of the life cycle and induction of male offspring. Even though Daphnia and many other aquatic invertebrates rely on sexual reproduction and subsequent production of dormant eggs to recover from environmentally harsh conditions, much less is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Recently, Navis et al. (2018) found evidence of marginal influence of fenoxycarb (an insecticide analogue of MF) on ephippia formation in D. magna . From a physiological point of view, male offspring and ephippia productions are regarded as two independent events allowing females to delay ephippia production in favour of parthenogenetic reproduction (De Meester & Vanoverbeke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Navis et al. (2018) found evidence of marginal influence of fenoxycarb (an insecticide analogue of MF) on ephippia formation in D. magna . From a physiological point of view, male offspring and ephippia productions are regarded as two independent events allowing females to delay ephippia production in favour of parthenogenetic reproduction (De Meester & Vanoverbeke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In daphniids, sex determination and sexual reproduction depend on environmental factors (Deng, 1996;Alekseev & Lampert, 2001;Slusarczyk, Ochocka, & Cichocka, 2012; see Glossary). Induction of sexual reproduction of females and production of males under laboratory conditions is influenced primarily by photoperiod (Stross & Hill, 1965;Kleiven, Larsson, & Hobaek, 1992), and at times by a second stimulus such as population density (Stross & Hill, 1965;Hobaek & Larsson, 1990), temperature (Stross, 1969;Korpelainen, 1986;Camp, Haeba, & LeBlanc, 2019), chemical cues (Slusarczyk, 1995;Pijanowska & Stolpe, 1996;Navis, Waterkeyn, De Meester, & Brendonck, 2018), or a combination of these factors (Kleiven et al, 1992). Current research progress into the genetic and molecular basis of sexual reproduction revealed candidate genes that are likely to facilitate the switch from parthenogenetic reproduction to sexual reproduction (Kato et al, 2008;Liu et al, 2014;Guo et al, 2015;Li et al, 2016), including the production of ephippial eggs and males (Kato, Kobayashi, Watanabe, & Iguchi, 2011;Xu et al, 2014;Guo et al, 2015).…”
Section: Ecological Modes Of Speciation: Habitat and Temporal Isolationmentioning
confidence: 99%
“…10,11 With the wide application of IGRs as insecticides, it has been found that RH-5849 is a moderately toxic insecticide, with a certain degree of damage to the genetic material of human peripheral blood lymphocytes; 12 excessive use of fenoxycarb will produce a certain reproductive toxicity to animals and lead to anemia in mammals. 13,14 To ensure food safety and human health, many countries and regions have set the maximum residue limit (MRL) standards for IGRs in food. The United States, EU, and Japan have published thousands of maximum residue limits (MRLs) for pesticides.…”
Section: Introductionmentioning
confidence: 99%